Modelling Adoption of Serious Games in Corporate Training: Analysis of Adoption Drivers - de Carvalho, Mathias Freire; de Oliveira Dias, Murillo (Archives of Business Research, 2025)
The growth of outsourced corporate training (OCT) services continues because organizations need to adapt to digital transformation and rising requirements for (re)skilling. The research investigates OCT digital serious game adoption and value through quantitative data analysis. The research used Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze survey data from n=200 US employees who received corporate-sponsored SG training through Amazon’s Mechanical Turk©. The results showed that five factors affect employee adoption behavior intention through their interest in learning and social influence and their ability to work flexibly and their expectations for success and their desire for enjoyment, revealing which organizational elements generate value in organizational digital Serious Games (SG), but these elements do not effectively support knowledge exchange, information sharing and innovation management. The research is supported by the UTAUT2 framework to confirm previous studies about organizations and SGs, while allowing practitioners to create people-oriented training approaches that use SGs as continuous learning resources.